2011
DOI: 10.1016/j.semcancer.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signaling and hepatocellular carcinoma

Abstract: Liver cancer is the fifth most common cancer and the third most common cause of cancer related death in the world. The recent development of new techniques for the investigations of global change in the gene expression, signaling pathways and wide genome binding has provided novel information for the mechanisms underlying liver cancer progression. Although these studies identified gene expression signatures in hepatocelluar carcinoma, the early steps of the development of hepatocellular carcinomas (HCC) are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 92 publications
2
57
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies and the third leading cause of cancer death in the world (Iakova et al, 2011). Of the total new cancer cases reported each year, HCC represents 7.9% in men and 6.5% in women (Ferlay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies and the third leading cause of cancer death in the world (Iakova et al, 2011). Of the total new cancer cases reported each year, HCC represents 7.9% in men and 6.5% in women (Ferlay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Two members of C/EBP family, C/EBP␣ and C/EBP␤, are expressed at high levels in the liver and are involved in the epigenetic control of liver proliferation and steatosis by interacting with p300 and HDAC1 (13)(14)(15). Studies with young and old mice suggested that the phosphorylation of C/EBP␣ at S193 is the major pathway of regulation of interactions of C/EBP␣ with HDAC1 (14).…”
mentioning
confidence: 99%
“…First, PLC/PRF/5 cells were plated onto 35-mm dishes at a density of 1x10 6 Transwell migration assay. PLC/PRF/5 cells were seeded in 96-well plates at a density of 1x10 4 cells/ml, incubated at 37˚C and added to the upper chamber of a Transwell membrane (Transwell Permeable Support with a 5.0-µm polycarbonate membrane, 6.5-mm insert and 24-well plate; Costar; Corning Life Sciences, Tewksbury, MA, USA).…”
Section: Hoechst 33258 Nuclear Staining For Evaluation Of Apoptosismentioning
confidence: 99%
“…Furthermore, the 5-year survival rate worldwide of HCC is still <5%, as a result of its high rate of recurrence and metastasis (5). HCC tumorigenesis is a complex Exogenous hydrogen sulfide promotes hepatocellular carcinoma cell growth by activating the STAT3-COX-2 signaling pathway multistep process that is closely associated with multiple signaling pathways and genes, and these factors can affect cell survival, proliferation, invasion and metastasis (6,7). The role of hepatitis B virus (HBV) or hepatitis C virus infection has been extensively investigated and considered as one of the reasons in the pathogenesis of HCC (8,9).…”
Section: Introductionmentioning
confidence: 99%